2023
DOI: 10.3389/fendo.2022.1065665
|View full text |Cite
|
Sign up to set email alerts
|

Integrated lipids biomarker of the prediabetes and type 2 diabetes mellitus Chinese patients

Abstract: IntroductionDyslipidemia is a hallmark of T2DM, and as such, analyses of lipid metabolic profiles in affected patients have the potential to permit the development of an integrated lipid metabolite-based biomarker model that can facilitate early patient diagnosis and treatment.MethodsUntargeted and targeted lipidomics approaches were used to analyze serum samples from newly diagnosed 93 Chinese participants in discovery cohort and 440 in validation cohort via UHPLC-MS and UHPLC-MS/MS first. The acid sphingomye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that increased levels of LPC with saturated FA, such as C14:0, act as proinflammatory mediators and are associated with inflammatory diseases. [95][96][97][98][99] Conversely, LPC 20:5 is typically considered anti-inflammatory mediator. 99 Regarding the sphingomyelin (SM) profile, this lipid class constitutes approximately 20% of total plasma phospholipids and is the most abundant sphingolipid class in lipoproteins, especially low-density lipoproteins (LDL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that increased levels of LPC with saturated FA, such as C14:0, act as proinflammatory mediators and are associated with inflammatory diseases. [95][96][97][98][99] Conversely, LPC 20:5 is typically considered anti-inflammatory mediator. 99 Regarding the sphingomyelin (SM) profile, this lipid class constitutes approximately 20% of total plasma phospholipids and is the most abundant sphingolipid class in lipoproteins, especially low-density lipoproteins (LDL).…”
Section: Discussionmentioning
confidence: 99%
“…While levels of LPC 14:0 and LPC 22:4(with a very low abundance) were found to be increased, the LPC 20:5 was decreased in MCADD children. Previous studies have demonstrated that increased levels of LPC with saturated FA, such as C14:0, act as pro‐inflammatory mediators and are associated with inflammatory diseases 95–99 . Conversely, LPC 20:5 is typically considered anti‐inflammatory mediator 99 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that Cer(d18:1/20:0) had a significant predictive value for the occurrence of type 2 diabetes in the healthy population. 30 , 31 And interventions in Cer(d18:1/14:0) and Cer(d18:1/16:0) may improve the outcomes of patients with type 2 diabetes. 32 , 33 It is revealed that very long chain ceramides (C24, C26, and C26:1) are associated with the development of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“… 85 Increased de novo ceramide synthesis in the endoplasmic reticulum can activate protein phosphatase 2A (PPA2), inactivate protein kinase B (Akt) in the insulin signaling pathway and ultimately inhibit insulin sensitivity and β-cell function. 86 As one of the most prominent phospholipid components in animal cell membranes, sphingomyelin has been observed to correlate inversely with GDM in several studies. 68 Furthermore, downregulated sphingolipid metabolism may be an early predictor of the transition from GDM to T2DM.…”
Section: Urine Metabolomicsmentioning
confidence: 99%